A new nano-worm structure from gold-nanoparticle mediated random curving of zinc oxide nanorods - Veeradasan Perumal; Uda Hashim; Subash C.B. Gopinath; R. Haarindraprasad; P. Poopalan; Wei-Wen Liu; M. Ravichandran; S.R. Balakrishnan; A.R. Ruslinda (Elsevier, 2024)
Biosensors and Bioelectronics Volume 78, 15 April 2016, Pages 14-22